(untitled) (مجلة إحالات, 2025)
تناقش ورقتنا البحثيّة نماذج نقديّة لنقاد عرب معاصرين عكفوا على قراءة رواية الأمير للروائي الجزائري واسيني الأعرج قراءة نقدية وسجاليّة. وقد اخترنا من أجل ذلك أربعة منظورات قرائية لرواية الأمير أنجزها كل من التونسي محمد القاضي والمغربي ادريس الخضرواي والجزائري اليامين بن تومي والسورية ماجدة حمود. This paper discusses some patterns of modern Arab critics who have read Waciny Laredj’s novel: Kitab El-Amir critically. We chose four perspective readings of the novel, which were performed by the Tunisian Mohamed El Kadi, the Moroccan Idriss Khadraoui, the Algerian Elyamine Ben toumi and the Syrian Majda Hamoud.